Outcomes in Pregnant Women with Valvular Heart Disease from Portuguese-Speaking African Countries Treated in Portugal through an International Agreement of Health Cooperation - Vera Vaz Ferreira; André Viveiros Monteiro; Rita Ilhão Moreira; Marta Plancha; Ana Isabel Machado; Alexandra Castelo; Pedro Garcia Brás; Tânia Branco Mano; Maria José Alves; Boban Thomas; Rui Cruz Ferreira; Lino Patrício (Ubiquity Press, 2023)
Aims: We performed a clinical audit of maternal and fetal outcomes in pregnant women with valvular heart disease (VHD) from Portuguese-speaking African countries who were transferred for their care, during a twenty-year period, through a memorandum of agreement of international cooperation. Methods and results: A retrospective analysis of 81 pregnancies in 45 patients with VHD (median age 24, interquartile range 22-29 years) from 2000 to 2020 was performed. The main outcome measures were maternal cardiovascular and fetal outcomes. History of rheumatic heart disease was present in 60 (74.1%) pregnancies. Most were in New York Heart Association (NYHA) functional class I or II; at the first evaluation, 35 (43.2%) were on cardiac medication and 49 (60.5%) were anticoagulated. Forty-eight pregnancies had at least one valvular prosthesis, including 38 mechanical heart valves. During pregnancy, deterioration in NYHA functional class occurred in 35 (42.0%), and eight (9.9%) patients required initiation or intensified cardiac medication. Mechanical valve thrombosis complicated four (4.9%) pregnancies, all cases on heparin, and resulted in one maternal death. Haemorrhagic complications happened in 7 (8.6%) anticoagulated patients, in the immediate postpartum or puerperal period. The 81 pregnancies resulted in 56 (69.1%) live births, while miscarriage and fetal malformations occurred in 19 (23.5%) and 12 (14.8%) pregnancies, respectively. In multivariate analysis, vitamin K antagonist therapy was the only independent predictor of an unsuccessful pregnancy (p = 0.048). Conclusion: In a high-income country, successful pregnancy was possible with low rate of maternal events in women with VHD transferred from five low-middle income countries in Africa. The use of anticoagulation with a vitamin K antagonist was associated with an unsuccessful pregnancy.